Cholesterol Metabolism in T Cells - Bietz, Andreas; Zhu, Hengyu; Xue, Manman; Xu, Chenqi (Frontiers in Immunology, 2017)
Compartmentalization and spatial control of biochemical reactions is the foundation of cell-based life on earth. The lipid bilayer system employed by eukaryote cells not only keeps them separate from the environment but also provides a platform for key receptors to sense and interact with outside factors. Arguably one of the cell types most reliant on interactions of this kind, immune cells depend on their membrane to keep functioning properly. In this review, the influence of variation in cholesterol levels, a key component of lipid bilayer stability, on T cells will be discussed in detail. In comparison to other cells, T cells must be able to undergo rapid activation followed by proliferation. Furthermore, receptor colocalization is an important mechanism in this activation process. The impact of cholesterol availability on the processes of T cell proliferation and receptor sensitivity, as well as its potential for immunomodulation in disease treatment will be considered.